Business resilience - Kemp, Mark (RIBA good practice guides., 2022)
Architecture can be a high risk and low-income profession. Planning to manage risks is essential. Workloads tend to be cyclical and managing lean periods and booms whilst being prepared for the next downturn is a key requirement.